ETNOGRAFI KOMUNIKASI TRADISI DOA KUBUAR HARI RAYA ENAM PADA SUKU MELAYU DI DESA KOTO TINGGI PANGEAN KECAMATAN PANGEAN KABUPATEN KUANTAN SINGINGI - Ramadhani, Tri Fitri Ramadhani; Salam, Noor Efni (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
The Doa Kubur Hari Raya Enam tradition is a cultural practice of the Malay community in Kuantan Singingi Regency, carried out on the 8th of Shawwal, with the purpose of strengthening social bonds, honoring ancestors, and reminding individuals of death and their return to Allah SWT. This study aims to examine the ethnography of communication in the Doa Kubur Hari Raya Enam tradition in Koto Tinggi Pangean Village, Pangean District, Kuantan Singingi Regency, focusing on communicative situations, communicative events, and communicative acts. This research employs a descriptive qualitative method with an ethnography of communication approach. Data were collected through interviews, observation, and documentation, and analyzed using Miles and Huberman’s interactive model, while data validity was ensured through triangulation. The findings indicate that the communicative situation in this tradition is characterized by the context of time, place, and a sacred atmosphere that strengthens social cohesion; communicative events include the stages of preparation, implementation, and closure; and communicative acts are manifested through symbolic verbal and nonverbal messages. Traditional leaders play a significant role in guiding communication, fostering empathy, togetherness, and the preservation of local cultural values. Keywords: Ethnography of Communication, Doa Kubur, Hari Raya Enam